The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1986
DOI: 10.1073/pnas.83.20.7726
|View full text |Cite
|
Sign up to set email alerts
|

Engineering of the mRNA-interfering complementary RNA immune system against viral infection.

Abstract: Creation of an artificial mRNA-interfering complementary RNA (micRNA) immune system, utilizing anti-sense RNAs to inhibit viral gene expression, has been shown to be an effective way to prevent viral infection. In the RNA coliphage SP, the gene for the maturation protein was found to be the best target for this type of immune system; mRNA-interfering complementary RNAs specific to the genes for coat protein and replicase were less effective in preventing infection. The greatest inhibitory effect was observed w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

1989
1989
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 15 publications
0
14
0
Order By: Relevance
“…It has been shown that replication ofthe RNA coliphage SP can be inhibited by antisense RNA by expressing various antisense viral sequences in the host (9,10). The antisense RNA for the maturase gene was the most effective molecule in these replication inhibition assays, and antisense RNA complementary to sequences at the 3' end of the viral RNA had a lesser effect.…”
mentioning
confidence: 95%
“…It has been shown that replication ofthe RNA coliphage SP can be inhibited by antisense RNA by expressing various antisense viral sequences in the host (9,10). The antisense RNA for the maturase gene was the most effective molecule in these replication inhibition assays, and antisense RNA complementary to sequences at the 3' end of the viral RNA had a lesser effect.…”
mentioning
confidence: 95%
“…Furthermore, RNA phages paved the way for antisense-based gene therapy via the generation of the so-called ‘mRNA-interfering complementary RNA (micRNA) immune system' for the prevention of phage SP proliferation [39,40]. …”
Section: Family Of Rna Phagesmentioning
confidence: 99%
“…Antisense approaches have been used previously in this system (38), but we believed more efficient ablation would be achieved using a ribozyme approach with catalytic efficiency. Considering that targeting the initiating AUG codon or adjacent sequences may increase the antisense effect of ribozymes (39,40), ribozyme-6 was chosen for transfection and expression in ROS 17/2.8 cells. Because the alternative splice that occurs in the osteoblast ␣ 1C mRNA is downstream in the coding region at transmembrane segments IVS3-IVS4 (11), ribozyme-6 was expected to cleave transcripts encoding both of these isoforms.…”
Section: Figmentioning
confidence: 99%